Operation control and dispatch optimization of distributed energy resources Part II - Dai, Li Jun (2010)
This project assumes that several energy resources have been set up as part of the Intelligent Energy Distributed System (IEDS). In order to achieve economic dispatch and test, control and monitor the different parameters of power apparatus, we need a tool or platform, called LabVIEW. LabVIEW is a graphical programming language. We can also use LabVIEW and hardwares from National Instruments to set up a SCADA system, through which, communications between different devices are made easy. These days, we place a lot of attentions to the renewable energy for future consideration. Wind energy becomes more and more popular. Here, we also want to address this issue on how to test, control and monitor the operating conditons of the wind turbine with LabVIEW and devices from National Instruments.